The difference in patterns of motor and cognitive function in chronic fatigue syndrome and severe depressive illness. - Lawrie, S; MacHale, S; Cavanagh, J; O'Carroll, R; Goodwin, G (2000)
BACKGROUND: Chronic fatigue syndrome (CFS) and major depressive disorder (MDD) share many symptoms and aetiological factors but may have different neurobiological underpinnings. We wished to determine the profile of the biological variables disturbed in CFS and MDD, and identify any critical factors that differentiate the disorders. METHODS: Thirty patients with CFS, 20 with MDD and 15 healthy controls matched group-wise for age and sex were recruited. Subjects were given a detailed battery of motor and cognitive tests, including measures of psychomotor speed, memory and maximal voluntary muscle contraction in both the morning and evening that were balanced to avoid order effects. RESULTS: CFS patients generally performed worse on cognitive tests than healthy controls, but better than patients with MDD. Both patient groups had markedly impaired motor function compared with healthy controls. MDD subjects showed a significantly greater diurnal improvement in maximal voluntary contraction than healthy controls. CONCLUSIONS: Patients with CFS and MDD show similarly substantial motor impairment, but cognitive deficits are generally more marked in MDD. Diurnal changes in some functions in MDD may differentiate the disorder from CFS.